2022
DOI: 10.3389/fgene.2022.923737
|View full text |Cite
|
Sign up to set email alerts
|

Pan-cancer analyses confirmed the cuproptosis-related gene FDX1 as an immunotherapy predictor and prognostic biomarker

Abstract: Background: The latest research identified cuproptosis as an entirely new mechanism of cell death. However, as a key regulator in copper-induced cell death, the prognostic and immunotherapeutic value of FDX1 in pan-cancer remains unclear.Methods: Data from the UCSC Xena, GEPIA, and CPTAC were analyzed to conduct an inquiry into the overall differential expression of FDX1 across multiple cancer types. The expression of FDX1 in GBM, LUAD and HCC cell lines as well as their control cell lines was verified by RT-Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 62 publications
4
32
0
Order By: Relevance
“…Another recent pan-cancers analysis also found that the FDX1 expression levels were down-regulated in tumor tissues of KIRC, ACC, HNSC, THCA, and LGG. In their pan-cancers analysis, FDX1 was considered to be a potential prognostic biomarker of immunotherapy due to its signi cant association with clinical characteristics, tumor mutational burden, microsatellite instability, immune-related signal pathways, immune cell in ltration, and antitumor drug susceptibility [17]. These results were consistent with our ndings.…”
Section: Discussionsupporting
confidence: 91%
“…Another recent pan-cancers analysis also found that the FDX1 expression levels were down-regulated in tumor tissues of KIRC, ACC, HNSC, THCA, and LGG. In their pan-cancers analysis, FDX1 was considered to be a potential prognostic biomarker of immunotherapy due to its signi cant association with clinical characteristics, tumor mutational burden, microsatellite instability, immune-related signal pathways, immune cell in ltration, and antitumor drug susceptibility [17]. These results were consistent with our ndings.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, lower expression of the FDX1 gene was reported to be closely associated with more advanced tumor-node-metastasis stages [161]. Furthermore, lower expression of FDX1 in various cancer types has been correlated with shorter survival times [13,162,163]. Despite these findings, cuproptotic events have not been well documented in diverse cancers.…”
Section: Cuproptosis In Proliferation and Metastasismentioning
confidence: 99%
“…Zhang C et al found that the expression of FDX1 has prognostic value for the survival of Adrenocortical Cancer (ACC), Kidney Clear Cell Carcinoma (KIRC), Head and Neck Cancer (HNSC), Thyroid Cancer (THCA), and LGG. In addition, the expression level of FDX1 was confirmed to be closely related to immune infiltration ( 75 ). Zhang Y. et al found that FDX1 is an independent prognostic factor and potential prognostic biomarker of WHO grade II/III glioma ( 76 ).…”
Section: Discussionmentioning
confidence: 96%